IMPLEMENTASI SISTEM INFORMASI REKAPITULASI ABSENSI PERKULIAHAN MAHASISWA PADA STIKOM DINAMIKA BANGSA - Marrylinteri (Jurnal PROCESSOR, 2021)
â€œAttendance is usually used as a marker of someone's presence in an activity or event. Attendance can be applied in various activities, one of which is in the world of education, namely attendance at teaching and learning activities. In terms of teaching at STIKOM Dinamika Bangsa it also applies an attendance system to students. Students do attendance in every lecture they take. Attendance is done by signing the attendance list paper provided by the academic. This attendance is used as a condition for students to take the final semester exams. Students who can take the final semester exams must take no less than 75% of the total number of meetings for each subject. To find out the number of student attendance in lectures, at the end of each semester the attendance will be recapitulated by the study program staff. Student lecture attendance data is inputted using the MS application. Excel. Recording student lecture attendance data using the MS application. This Excel raises several problems. For example, BAAK takes a long time to make announcements on the names of students who cannot take the final semester exams, it requires a lot of paper to make announcements for students who cannot take the final semester exams, students will also be late in getting information about the final semester examination room. With this research, it has resulted in an information system application that can assist BAAK in processing student lecture attendance recapitulation data and help students to get lecture attendance recapitulation information and final semester exam room information.â€